Control and Measurement of Quantum Light Pulses for Quantum Information Science and Technology. Issue 9 (23rd July 2021) - Karpiński, Michał; Davis, Alex O. C.; Sośnicki, Filip; Thiel, Valérian; Smith, Brian J.
Abstract: Manipulation of quantum optical pulses, such as single photons or entangled photon pairs, enables numerous applications, from quantum communications and networking to enhanced sensing. Common methods to shape laser pulses based upon filtering or amplification cannot be employed with quantum light pulses as these approaches introduce detrimental loss and noise to the system. Here, methods to control and measure quantum light pulses based upon deterministic application of targeted phases in time and frequency domains are reviewed, along with recent demonstrations of quantum applications. Abstract : Temporal‐spectral properties of quantum light are a promising platform for optical quantum technologies. Here, approaches to control and measure quantum light pulses by applying targeted spectral and temporal phase modulation are reviewed. Quantum applications that have been enabled by these approaches to precisely control time–frequency characteristics are highlighted and future directions for quantum technologies harnessing temporal‐mode encoding are discussed.